A microfluidic chip for immobilization and imaging of Ciona intestinalis larvae - Poncelet, G; Parolini, L; Shimeld, SM (Wiley, 2024)
Sea squirts (Tunicata) are chordates and develop a swimming larva with a small and defined number of individually identifiable cells. This offers the prospect of connecting specific stimuli to behavioral output and characterizing the neural activity that links these together. Here, we describe the development of a microfluidic chip that allows live larvae of the sea squirt Ciona intestinalis to be immobilized and recorded. By generating transgenic larvae expressing GCaAMP6m in defined cells, we show that calcium ion levels can be recorded from immobilized larvae, while microfluidic control allows larvae to be exposed to specific waterborne stimuli. We trial this on sea water carrying increased levels of carbon dioxide, providing evidence that larvae can sense this gas.